Monstera Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
HS-1071, a 5-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a basic reference for growing monstera in the home landscape. Includes a table of suggested cultural practices by month. Published by the UF Department of Horticultural Sciences, February 2006.